ISLAMIC LAW REVIEW ON BUYING AND SELLING SNAKES AS TERTIARY NEEDS - Husni A.Jalil; Riko Alkausar (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2019)
The process of buying and selling in social relations between several individuals requires the existence of contracts and procedures to fulfil the provisions of the validity of the sale and purchase. One of the forms of buying and selling carried out by the general public is the buying and selling of snakes, which must fulfil the criteria and classification of buying and selling in the review of Islamic economic law. The hobby or pleasure of keeping snakes as a tertiary need in order to get reciprocal psychological pleasure for the Wildlife Lovers Community and society in general, but this often causes irregularities and gaps for both the snake keeper and the snake, In this study, the focus of research is on how the procedure of buying and selling snakes in Petshop Banda Aceh, how the fiqh muamalah review of buying and selling snakes in petshop Banda Aceh, how the sadduz zhariah review of the hobby and or maintenance of snakes as tertiary needs or Al-Taḥsīnīyyah. The research method used is descriptive analysis and data collection is done by library research and field research, with data collection techniques by interview and documentation. Based on the analysis that has been done, the snake trading transaction procedure has not met the criteria of a muamalah contract, the fiqh muamalah review of snake trading is not in accordance with the legal classification of buying and selling contained in syarak law, according to the Sadduz zhariah review of snake maintenance as a tertiary need or Al-Taḥsīnīyyah should not be done because it can cause greater mafsadat than maslahat, so that the legal consequences contained in the sadduz zhariah method become fasid or void for snake maintenance in the Wildlife Lovers Community and society in general.